Attempting to Detect a Lie: Do We Think it Through? - Iuliia Grabova; Hedda Nielsen; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Game-theoretic analyses of communication rely on beliefs – especially, the receiver's belief about the truth status of an utterance and the sender's belief about the reaction to the utterance – but research that provides measurements of such beliefs is still in its infancy. Our experiment examines the use of second-order beliefs, measuring belief hierarchies regarding a message that may be a lie. In a two-player communication game between a sender and a receiver, the sender knows the state of the world and has a transparent incentive to deceive the receiver. The receiver chooses a binary reaction. For a wide set of non-equilibrium beliefs, the reaction and the receiver's second-order belief should dissonate: she should follow the sender's statement if and only if she believes that the sender believes that she does not follow the statement. The opposite is true empirically, constituting a new pattern of inconsistency between actions and beliefs.
Keywords: D01; D83; 330; strategic information transmission; lying; higher-order beliefs